Laminoplasty versus laminectomy with fusion for treating multilevel degenerative cervical myelopathy - Oussama Bakr, MS; Khadija Soufi, BS; Quincy Jones, BS; Barry Bautista, BS; Benjamin Van, MD; Zachary Booze, BS; Allan R. Martin, MD, PhD; Eric O. Klineberg, MD; Hai Le, MD; Julius O. Ebinu, MD, PhD; Kee D. Kim, MD; Yashar Javidan, MD; et al. (North American Spine Society Journal, 2023)
Background: Laminectomy with fusion (LF) and laminoplasty (LP) are common posterior decompression procedures used to treat multilevel degenerative cervical myelopathy (DCM). There is debate on their relative efficacy and safety for treatment of DCM. The goal of this study is to examine outcomes and costs of LF and LP procedures for DCM. Methods: This is a retrospective review of adult patients (<18) at a single center who underwent elective LP and LF of at least 3 levels from C3-C7. Outcome measures included operative characteristics, inpatient mobility status, length of stay, complications, revision surgery, VAS neck pain scores, and changes in radiographic alignment. Oral opioid analgesic needs and hospital cost comparison were also assessed. Results: LP cohort (n=76) and LF cohort (n=59) reported no difference in neck pain at baseline, 1, 6, 12, and 24 months postoperatively (p>.05). Patients were successfully weaned off opioids at similar rates (LF: 88%, LP: 86%). Fixed and variable costs respectively with LF cases hospital were higher, 15.7% and 25.7% compared to LP cases (p=.03 and p<.001). LF has a longer length of stay (4.2 vs. 3.1 days, p=.001). Wound-related complications were 5 times more likely after LF (13.6% vs. 5.9%, RR: 5.15) and C5 palsy rates were similar across the groups (LF: 11.9% LP: 5.6% RR: 1.8). Ground-level falls requiring an emergency department visit were more likely after LF (11.9% vs. 2.6%, p=.04). Conclusions: When treating multilevel DCM, LP has similar rates of new or increasing axial neck pain compared to LF. LF was associated with greater hospital costs, length of stay, and complications compared to LP. LP may in fact be a less morbid and more cost-effective alternative to LF for patients without cervical deformity.